Why Does Cysteine Enhance Metal Uptake by Phytoplankton in Seawater but Not in Freshwater? - Liu,F; Tan,Q-G; Fortin,C; Campbell,PGC (Environ Sci Technol, 2019)
Low-molecular-weight weak ligands such as cysteine have been shown to enhance metal uptake by marine phytoplankton in the presence of strong ligands, but the effect is not observed in freshwater. We hypothesized that these contrasting results might be caused by local cysteine degradation and a Ca effect on metal-ligand exchange kinetics in the boundary layer surrounding the algal cells; newly liberated free metal ions cannot be immediately complexed in seawater by Ca-bound strong ligands but can be rapidly complexed by free ligands at low-Ca levels. The present results consistently support this hypothesis. At constant bulk Cd2+ concentrations, buffered by strong ligands: (1) at 50 mM Ca, cysteine addition significantly enhanced Cd uptake in high-Ca preacclimated euryhaline Chlamydomonas reinhardtii (cultured with cysteine as a nitrogen source to enhance local Cd2+ liberation via cysteine degradation); (2) at 0.07 mM Ca, this enhancement was not observed in the algae; (3) at 50 mM Ca, the enhancement disappeared when C. reinhardtii were cultured with ammonium (to inhibit cysteine degradation and local Cd2+ liberation); (4) cysteine addition did not enhance Cd uptake by cysteine-cultured marine Thalassiosira weissflogii when the concentration of immediately reacting strong ligands was sufficient to complex local Cd2+ liberation.